1986
DOI: 10.1088/0266-5611/2/1/004
|View full text |Cite
|
Sign up to set email alerts
|

The circular harmonic Radon transform

Abstract: The circular harmonic decomposition method for evaluating the inverse Radon transform is investigated. A discrete, finite set of projection data may be aliased and its interpretation is inevitably non-unique. When the inverse Radon transform is approximated by a summation, the filtered back projection, it is shown that as well as being non-unique, the reconstruction is inconsistent with the data. By contrast, the circular harmonic decomposition produces a consistent image. The stable form of the method is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…As we have shown, it is sufficient develop a single reconstruction algorithm for the Radon transform on circles passing through a fixed point, since all other cases can be reduced to that one by a change of variable and a change of functions. Since we use the formalism of angular Fourier components, we shall adapt a procedure set up long ago by C. H. Chapman & P. W. Carey [12] for the classical Radon transform.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…As we have shown, it is sufficient develop a single reconstruction algorithm for the Radon transform on circles passing through a fixed point, since all other cases can be reduced to that one by a change of variable and a change of functions. Since we use the formalism of angular Fourier components, we shall adapt a procedure set up long ago by C. H. Chapman & P. W. Carey [12] for the classical Radon transform.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Here ı IRU PRGDOLW\ 7KDQNV WR WKH NH\ IRUPXOD > @ (9) the inversion of (8) can be achieved by a clever application of (9). The resulting explicit inversion formula reads (10) However (10), as such is still improper for setting up a computational algorithm.…”
Section: Chebyshev Integral Transformsmentioning
confidence: 99%
“…In practice a computing algorithm can be set up from (11) following the approach of Chapman and Carey [9]. It FRQVLVWV LQ FXWWLQJ WKH IJ-integration range into a finite number of integrals and then making the proper change of variables so that each term is represented by an exactly calculated indefinite integral.…”
Section: Remarkmentioning
confidence: 99%
“…Then he derived a consistency condition for the data which permits to regularize the inverse formulas. From the regularized formulas, Chapman and Cary [11] discussed an alternative inversion algorithm to the 'Filtered Back-Projection' (FBP) algorithm for the standard Radon transform (RT) and showed that the fulfilment of the consistency criterion of the data reduces the number of artefacts. This is not so in the well-known FBP algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the CHD approach has not been widely used for image reconstruction. However, this approach offers many advantages, in particular in the case of Radon data [9][10][11], for example consistency between the image reconstruction formula and the data, stable algorithms, reduced artefacts, less complexity in algorithms and less computing time.…”
Section: Introductionmentioning
confidence: 99%